Florida Public Health Association 2009 Survey of Academic Public Health Programs in Florida - Leslie Sue Lieberman; Nancy Rudner Lugo; Mary Peoples-Sheps; Melissa J. Vilaro; Claude Earl Fox (University of North Florida, 2011)
Preparing the public health workforce is essential to the protection ofthe health and wellbeing ofthe state and the nation. Yet, a workforce shortage is looming. It is anticipated that by 2020, the nation will be facing a shortfall ofmore than a quarter of a million public health workers. To address this impeding shortage, the Association of Schools of Public Health (ASPH) has stressed the need to build public health education capacity, with emphasis on competencies and curriculum in emerging diseases, with joint degrees, and with diverse approaches to education, including certificates and distance learning. To assess Florida's available public health professional preparation programs in meeting workforce needs, the Academic Committee ofthe Florida Public Health Association (FPHA) undertook a survey of the nine public and private universities offering the MPH degree in the state.